B3 Waste Management and Health Workers Complaint In. Inka (Persero) Madiun City - Tentrami Hayuning Ichtiakhiri; Sudarmaji Sudarmaji (Universitas Airlangga, 2015)
Abstract: Disposal of industrial products containing chemical compounds especially harmful and toxic material negative impact on the environment and human health. PT. INKA (Persero) is a company engaged in manufacturing and railway services generating B3 waste from the production process.. B3 waste is used oil/oil cooler scars, B3 cans (cans of paint, thinner, drums), used batteries, sand ex. blasting, dust ex. blasting, plasma crust, former rags, waste fiber glass. B3 waste containing various heavy metals such as Pb, Cu, Hg, and Fe. This can be avoided by doing the B3 waste management in industry. The purpose of this research is describing the implementation of B3 waste management and perceived health complaints of workers. This research is a descriptive cross-sectional design. The sample of respondents was taken by total sampling with a sample size of 10 workers B3 waste management. The research variables are B3 waste management (sorting, storage, collection, transportation, utilization, processing, stockpiling) and health complaints. The results showed that PT. INKA (Persero) has not qualified in terms of B3 waste management such as sorting and storage. Health complaints are often perceived by employees is a headache and skin irritation. In this research required the supervision of B3 waste management in PT. INKA (Persero) as well as increased awareness of workers to wear protective equipment to manage waste.Keywords: B3 Waste Management, Health Complaints